2021
DOI: 10.1111/ppe.12831
|View full text |Cite
|
Sign up to set email alerts
|

The association between late preterm birth and cardiometabolic conditions across the life course: A systematic review and meta‐analysis

Abstract: This is an open access article under the terms of the Creat ive Commo ns Attri butio n-NonCo mmerc ial-NoDerivs License, which permits use and distribution in any medium, provided the original work is properly cited, the use is non-commercial and no modifications or adaptations are made.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
11
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 19 publications
(11 citation statements)
references
References 84 publications
(309 reference statements)
0
11
0
Order By: Relevance
“…In population-based studies, a 2-fold increase in the prevalence of type 2 diabetes has been noted by 40 to 60 years of age in infants born preterm [ 23 , 26 ]. In a recent meta-analysis, infants born preterm had a higher risk of diabetes and hypertension as adults [ 27 ]. Early diagnosis and management of prediabetes would contribute not only to decrease the disease progression towards type 2 diabetes [ 28 ] but also in reducing cardiovascular morbidity in these infants [ 29 ].…”
Section: Risk For Cardiovascular Diseasementioning
confidence: 99%
“…In population-based studies, a 2-fold increase in the prevalence of type 2 diabetes has been noted by 40 to 60 years of age in infants born preterm [ 23 , 26 ]. In a recent meta-analysis, infants born preterm had a higher risk of diabetes and hypertension as adults [ 27 ]. Early diagnosis and management of prediabetes would contribute not only to decrease the disease progression towards type 2 diabetes [ 28 ] but also in reducing cardiovascular morbidity in these infants [ 29 ].…”
Section: Risk For Cardiovascular Diseasementioning
confidence: 99%
“…However, studies on growth in preterm cohorts across key stages of growth development [ 33 ] and at more advanced GA are scarce [ 10 , 20 , 34 ]. Several methodological considerations and sample characteristics complicate the interpretation and comparability of findings on the relationship between GA with later body size [ 5 , 6 , 35 , 36 , 37 ]. These include differences in study design; using birth weight as a proxy for GA; sample size; age at outcome; conditions under which variables are examined; type of statistical analysis; and availability of confounders.…”
Section: Introductionmentioning
confidence: 99%
“…Confounding variables were selected a priori based on previous literature 11 and conceptualized using a directed acyclic graph (eFigure 2 in the Supplement) that included maternal, perinatal, child, and sociodemographic characteristics hypothesized to be associated with both gestational age at birth and child's CMR but not on the causal pathway. Confounding variables were maternal age at birth, ethnicity, prepregnancy BMI, prepregnancy diabetes, prepregnancy hypertension, gestational diabetes, gestational hypertension, preeclampsia or eclampsia, venous thromboembolism, annual family income, and family history of cardiometabolic conditions or risk factors.…”
Section: Confounding Variablesmentioning
confidence: 99%
“…8 Size for gestational age, a measure that incorporates infant size at birth, has also been acknowledged as having an impact for health later in life through altered childhood growth and overweight status. 9,10 A systematic review 11 examining the association between late preterm birth and cardiometabolic health outcomes suggested that children younger than 18 years who were born late preterm vs term were at increased risk of diabetes (pooled adjusted risk ratio from 9 studies: 1.24 [95% CI, 1.17-1.32]) and hypertension (pooled adjusted risk ratio from 11 studies: 1.21 [95% CI, 1.13-1.30]). Studies 12,13 have also found that adults born late preterm compared with term had high levels of cardiometabolic risk (CMR) factors, including higher body fat percentage, higher blood pressure, metabolic syndrome, and stroke.…”
Section: Introductionmentioning
confidence: 99%